PERSEPSI MAHASISWA TERHADAP RAGAM ASESMEN DI PERKULIAHAN - Purwasih, Joan Hesti Gita; Pratiwi, Seli Septiana; Meiji, Nanda Harda Pratama; Apriyadi, Deny Wahyu; Hanindraputri, Eufrasia Kartika (Jurnal Visi Ilmu Pendidikan, 2024)
This research was conducted to determine perceptions and preferences for the forms of assignments that students expect and usually receive during lectures. The research used quantitative methods; the respondents are 118 students from UM Sociology Education. Through this research, lecturers can obtain initial diagnostic data, which researchers can use as considerations before planning the Semester Learning Plan (RPS). Therefore, the teaching process can accommodate government directions regarding team-based projects and student preferences. Apart from that, this survey also reflects on the lectures that lecturers have carried out so far. As a result, there was no significant difference in preferences between individual and group assignment forms. The form of article writing is the form of assessment for Mid-Semester Exams and Final Exams that lecturers often use, while most students prefer the form of product assessment. Over 50% of students did not support team teaching in one course.